MOTIVATIONS TO FORM A MAJORITY COALITION OF CANDIDATES MACHFUD ARIFIN AND MUJIMAN IN THE SURABAYA CITY ELECTION IN 2020 - Moh Ainul Yaqin (Politea : Jurnal Politik Islam, 2021)
The formation of a coalition of political parties in the regional head election is an interesting phenomenon to be studied, as was the case in the 2020 Surabaya City Election. The process of forming a coalition of political parties with the majority supporters of Machfud Arifin – Mujiaaman. Thus, this study analyzes the process of forming political party coalitions in the 2020 Surabaya City Election. This study uses Geoffrey Pridham's motivational theory of coalition formation regarding the factors that can influence the formation of political party coalitions, political coalition theory by William Riker which emphasizes (minimum winning) coalition) and rational choice theory to see the basic interests of the actors in determining the coalition. This study uses a qualitative approach, with interview data collection techniques and documentation studies. The findings of this study indicate that the process of forming a coalition supporting Machfud Arifin – Mujiaman begins with a strategic discourse between Gerindra, PKB, PAN, NasDem, PPP, Golkar, Democrats, and PKS which is oriented towards a tactical orientation to subvert the dominance of PDIP power in Surabaya. These parties basically have the same spirit because post-reform Surabaya has always been dominated by leaders from the PDIP. Machfud Arifin is considered a potential candidate because he has the financial strength, political networks, and inter-party lobbying in building coalition partners. Machfud Arifin became a trigger in the process of forming the coalition. In the process, horizontal-vertical dynamics occurred, because each party encouraged its cadres to become Machfud Arifin's companion. Thus, theoretically, the process of forming a coalition supporting Machfud Arifin - Mujiaman is influenced by three basic things, namely ideological factors which are the initial thoughts of the majority party which emphasizes leadership renewal, then the historical party that has existed since before 2020 elections were held and finally pragmatic factors ambition to gain power by merging eight political parties. In addition, political actors carry Machfud Arifin with rational choices, that first is the electability survey number, financial capital, and political network owned by the candidate. The coalition is dynamic, so it requires the same commitment and vision, as well as conflict management mechanisms to maintain the integrity of the coalition of political parties.